Pengaruh Model Pembelajaran Search, Solve, Create, Share (SSCS) Terhadap Civic Skills Peserta Didik dalam Pembelajaran Pendidikan Pancasila (Studi Kuasi Eksperimen di Kelas VII SMP PGRI Suryakencana Tahun Ajaran 2024/2025): Penelitian - Malika Kamilatul Maharani; Kokom Komalasari; Pitria Sopianingsih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to clearly and more detailed describe the extent of the influence of the SSCS learning model on students' civic skills, which will be applied in class VII.7 of SMP PGRI Suryakencana. This study uses a quantitative method with an experimental research design. The non-probability sampling method used in this study is purposive sampling. The criteria for the sample are students in Grade VII of SMP PGRI Suryakencana, consisting of 7 classes from Grade VII.1 to VII.7, with a total of 271 students. Data collection techniques include tests and questionnaires. The data analysis and test results in this study calculate the Normalized Gain (N-Gain) using the SPSS application program. The results of the study indicate that students demonstrate high levels of enthusiasm throughout each stage of the SSCS process, from gathering information, designing solutions, creating products, to presenting the results. This model is effective and helps students develop social skills such as communication skills, group collaboration, and problem-solving, which are part of civic skills.